2014
DOI: 10.1002/cmmi.1583
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of prostate tumors with 18F‐Al‐NOTA‐MATBBN

Abstract: Overexpression of the gastrin-releasing peptide receptor (GRPR) in prostate cancer provides a promising target for detection the disease. MATBBN is a new bombesin analog originating from the GRPR antagonists with a hydrophilic linker. In this study NOTA-conjugated MATBBN was labeled by the Al(18)F method and the potential of (18)F-Al-NOTA-MATBBN for prostate tumor PET imaging was also evaluated. NOTA-MATBBN was radiolabeled with (18) F using Al(18)F complexes. Partition coefficient, in vitro stability and GRPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…21 It may limit the potential for clinical application since the liver is a common metastatic site of cancer. A novel hydrophilic linker, Gly-Gly-Gly-Arg-Asp-Asn, significantly decreased the abdominal background at early time (nearly 30min) postinjection and efficiently improved the imaging qualities 24,25,26. Thus, we hypothesized that a modified cysteinylated ZHER 2:342 affibody with the linker, denoted as MZHER 2:342 , might possess more favorable in vivo pharmacokinetic performances.…”
Section: Introductionmentioning
confidence: 99%
“…21 It may limit the potential for clinical application since the liver is a common metastatic site of cancer. A novel hydrophilic linker, Gly-Gly-Gly-Arg-Asp-Asn, significantly decreased the abdominal background at early time (nearly 30min) postinjection and efficiently improved the imaging qualities 24,25,26. Thus, we hypothesized that a modified cysteinylated ZHER 2:342 affibody with the linker, denoted as MZHER 2:342 , might possess more favorable in vivo pharmacokinetic performances.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the fact that BBN can remarkably enhance NPs uptake through GRPR-mediated endocytosis. 21 Moreover, fluorescence microscopy images showed that Gd 2 O 3 -FI-PEG-BBN fluorescence was predominantly accumulated in the cytoplasm around the nucleus.…”
Section: Specificity Of Targeting Pc-3 Cells In Vitromentioning
confidence: 99%
“…10 min static PET scans were acquired at 30 min, 1, and 2 h after injection. Analytic methods of image were according to the study of Xu, Pan, et al [26,28]. The images were reconstructed using a three-dimensional ordered subset expectation maximum (OSEM) algorithm, and no correction was applied for attenuation or scatter.…”
Section: Small-animal Petmentioning
confidence: 99%